2001
DOI: 10.1002/app.1423
|View full text |Cite
|
Sign up to set email alerts
|

Microporous membranes prepared from blends of polysulfone and sulfonated poly(2,6‐dimethyl‐1,4‐phenylene oxide)

Abstract: ABSTRACT:Membranes were prepared from solutions containing Udel-type polysulfone (PSf) and sulfonated poly(2,6-dimethyl-1,4-phenylene oxide) (SPPO). Polymer solutions in 1-methyl-2-pyrrolidone were cast on a nonwoven textile and precipitated in a water bath. The permeabilities and selectivities of the prepared membranes depended on the concentrations of both polymers in the casting solution. The higher the concentration of PSf, the lower were the permeabilities to water and average pore sizes of the membranes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Poly(2,6‐dimethyl‐1,4‐phenylene oxide) (PPO) is a well‐known engineering thermoplastic that has excellent thermal and mechanical properties, good electrical characteristics, good film formability, and high oxidation resistance 9. PPO can be modified by various chemical reactions including bromination, carboxylation, sulfonation, and acylation.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(2,6‐dimethyl‐1,4‐phenylene oxide) (PPO) is a well‐known engineering thermoplastic that has excellent thermal and mechanical properties, good electrical characteristics, good film formability, and high oxidation resistance 9. PPO can be modified by various chemical reactions including bromination, carboxylation, sulfonation, and acylation.…”
Section: Introductionmentioning
confidence: 99%
“…These polymers usually show good thermal and mechanical properties, and they have reported that a wide spectrum of characteristics can be obtained by balancing the various groups . Moreover, these polymers are of increasing technological importance: in particular, poly(arylene ether sulfone)s (PAES)s have importance and are used in many fields, for instance as adhesives for metal‐to‐metal bonds, as membranes in the separation of gases and solids from solutions, as membranes for ultrafiltration and pervaporation or electrodialysis and, recently also, as toughening agents for brittle thermosets …”
Section: Introductionmentioning
confidence: 99%
“…In the 1980s, Kesting et al did systematic research on blending systems of CA and Nylon RO membranes8–10 and obtained important results. During the past two decades, studies on novel alloy membrane systems have been widespread,11–20 all of them indicating that alloy membranes provide a very effective and promising approach to modifying both the chemical and the physical structure of membranes, as well as controlling membrane performance. Consequently, many membrane properties can now be significantly improved, including permeability, selectivity, hydrophilicity, fouling resistance, bacteriological resistance, and mechanical strength.…”
Section: Introductionmentioning
confidence: 99%